A Tikhonov-Type Regularization Method for Identifying the Unknown Source in the Modified Helmholtz Equation. (24th December 2012) - Gao, Jinghuai; Wang, Dehua; Peng, Jigen
Abstract : An inverse source problem in the modified Helmholtz equation is considered. We give a Tikhonov-type regularization method and set up a theoretical frame to analyze the convergence of such method. A priori and a posteriori choice rules to find the regularization parameter are given. Numerical tests are presented to illustrate the effectiveness and stability of our proposed method.